Macroeconomic determinants on fossil fuel energy consumption in six ASEAN countries - Silfani, Dwi; Rozaini, Noni (Optimum: Jurnal Ekonomi dan Pembangunan, 2026)
ASEAN countries continue to face challenges in reducing their dependence on fossil fuels despite rapid economic growth and the ongoing global energy transition. This study examines how government expenditure, trade openness, and economic growth influence fossil fuel energy consumption in six ASEAN countries. Understanding the macroeconomic dynamics that drive fossil fuel use is critical for achieving international climate targets under the Paris Agreement, particularly as the region is among the fastest-growing in terms of energy demand and serves as a major global industrial base. Using panel data for the period 2001–2024 and a fixed effects model (FEM), the results show that economic growth has a positive but statistically insignificant effect on fossil fuel consumption, while trade openness and government expenditure have positive and statistically significant effects. These variables jointly explain approximately 98.28% of the variation, indicating that trade integration and fiscal expansion play a more dominant role than economic growth alone. These findings suggest that ASEAN’s reliance on fossil fuels is closely linked to trade dynamics and fiscal policy. Therefore, for regional economic integration to support the transition toward a sustainable energy system, trade and government spending policies must be aligned with energy efficiency and sustainability objectives.